2007
DOI: 10.1890/05-1879
|View full text |Cite
|
Sign up to set email alerts
|

Cavitation Resistance Among 26 Chaparral Species of Southern California

Abstract: Resistance to xylem cavitation depends on the size of xylem pit membrane pores and the strength of vessels to resist collapse or, in the case of freezing-induced cavitation, conduit diameter. Altering these traits may impact plant biomechanics or water transport efficiency. The evergreen sclerophyllous shrub species, collectively referred to as chaparral, which dominate much of the mediterranean-type climate region of southern California, have been shown to display high cavitation resistance (pressure potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
238
9
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 232 publications
(280 citation statements)
references
References 92 publications
(173 reference statements)
29
238
9
4
Order By: Relevance
“…High photosynthetic rates and the correspondingly high stomatal conductance must be supported by high hydraulic conductance (Mencuccini and Comstock 1999;Hubbard et al 2001;Sellin and Kupper 2007). Under optimal soil water supply, high K As allows more efficient water transport from stems into photosynthetic organs to compensate leaf water loss and consequently maintain daily water potential high (Ackerly 2004;Jacobsen et al 2007b). However, in this study there was no significant correlation among sapwood area: photosynthetic area ratio (A S :A P ) and K As .…”
Section: Morphological Traits Among Speciescontrasting
confidence: 56%
See 1 more Smart Citation
“…High photosynthetic rates and the correspondingly high stomatal conductance must be supported by high hydraulic conductance (Mencuccini and Comstock 1999;Hubbard et al 2001;Sellin and Kupper 2007). Under optimal soil water supply, high K As allows more efficient water transport from stems into photosynthetic organs to compensate leaf water loss and consequently maintain daily water potential high (Ackerly 2004;Jacobsen et al 2007b). However, in this study there was no significant correlation among sapwood area: photosynthetic area ratio (A S :A P ) and K As .…”
Section: Morphological Traits Among Speciescontrasting
confidence: 56%
“…These results suggest that changes in xylem anatomy (i.e., vessel size and density) among species could be related to plant functional strategies. Previous studies have suggested that there may be a range of ecologically significant vessel strategies available to species (Ackerly 2004;Preston et al 2006;Jacobsen et al 2007b).…”
Section: Morphological Traits Among Speciesmentioning
confidence: 99%
“…The stem segmentation index S and integration index F were not significantly correlated with each other (n ϭ 61; r ϭ Ϫ0.207; P ϭ .109; PICs: n ϭ 52; r ϭ Ϫ0.224; P ϭ .088). Stem-splitting shrubs compared with nonsplitting shrubs from dry environments ( Table 3) had higher vessel densities, smaller vessel hydraulic diameters, higher wood densities, and higher vessel implosion resistance, indicating strong resistance to drought-induced embolism formation (7,13,32).…”
Section: Resultsmentioning
confidence: 99%
“…completely air filled; Utsumi et al, 1999Utsumi et al, , 2003Ball et al, 2006). Generally, woody plants have excellent adaptable water-conducting systems that enable them to survive through the seasonal stresses of the regional climates in which they grow (Sperry et al, 1994;Maherali et al, 2004;Jacobsen et al, 2007). However, some pathogens (e.g.…”
mentioning
confidence: 99%